Value and Servitization: Creating Complex Deployed Responsive Services1. (August 2014) - Parry, Glenn; Tasker, Paul
<x xml:space="preserve">Abstract</x> A value framework can be used to describe the servitization transformation from traditional manufacturing business model to the current endpoint of a complex deployed responsive service delivered within the customer's dynamic environment, where the ability to capture worth is determined by the success of the customer.